Legal Analysis of Online Selling and Buying During Friday Sermons Perspective of The Syafi'i Mazhab - Matondang, Firman; Hidayat, Rahmat (JOM, 2024)
The transfer of land rights in Indonesia is governed by various positive laws currently in force. This research aims to analyze the law of online buying and selling during Friday sermons from the perspective of the Syafi'i School of Islamic jurisprudence. The focus is on transactions conducted through various online platforms or direct orders via private channels during Friday worship. Case studies were conducted in several mosques in the Medan Maimun District of Medan City, where many congregants were observed engaging in online transactions, thereby ignoring the sermon.The study employs a conceptual approach combined with living case studies to determine whether the legal ruling for online transactions during Friday sermons aligns with those conducted offline. Data were collected through observations and interviews with congregants who participated in online transactions during the sermons.The findings indicate that while online transactions conducted during Friday sermons are legally valid according to the Syafi'i School, they are considered Makruh (undesirable). This ruling applies because these actions distract individuals from the obligatory act of listening to the Friday sermon. Consequently, participants who engage in such transactions are deemed sinful for neglecting the sermon, as the primary obligation during this time is to pay attention to the sermon delivered by the Imam. The study highlights the need for greater awareness and adherence to religious obligations during Friday worship to maintain the sanctity and purpose of the sermon.